Comprehensive Genetic Analysis and Structural Characterization of CYP21A2 Mutations in CAH Patients - Carvalho, B.; Pereira, M.; Marques, C. J.; Carvalho, D.; Leão, M.; Oliveira, J. P.; Barros, A.; Carvalho, F. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Congenital Adrenal Hyperplasia (CAH) due to 21-hydroxylase deficiency is a common autosomal recessive disorder caused by mutations in the steroid 21-hydroxylase gene (CYP21A2). Complete DNA sequencing of CYP21A2 was performed in 5 patients, 3 non-classic and 2 classic forms of the disease, that were previously screened for the 10 most common mutations, in order to detect additional mutations that could justify the phenotype of the patients. 5 mutations were identified with the whole gene extended analysis. The mutations, p.Pro432Leu and p.Ala434Glu, the first previously reported by our group and the second a novel one were structurally analyzed with ICM-Pro software regarding biochemical properties such as protein stability, accessibility to surface and hydrophobicity, in order to elucidate their effects on the CYP21A2 protein. The 2 affected residues, Pro432 and Ala434, were also studied for conservation purposes in order to predict the severity of both mutations with PolyPhen-2 software and were considered as “probably damaging”. Prediction of clinical severity, based on molecular modelling and sequence conservation, was in accordance with the patient’s clinical diagnosis.
Keywords: CYP21A2; congenital adrenal hyperplasia; 21-hydroxylase; novel mutation